2011
DOI: 10.1265/jjh.66.608
|View full text |Cite
|
Sign up to set email alerts
|

An Occupational Physician-Pharmacist Cooperative Management for Hypertension by the Use of Educational Letters and Posters

Abstract: Objectives: To provide an occupational physician-pharmacist cooperative management for hypertension, we aimed to improve blood pressure (BP) control for workers with high-normal BP or hypertension.Method Office systolic and diastolic BP decreased after the hypertension management by the use of educational letters and posters (−3.1 mmHg; p<0.001, −1.5 mmHg; p=0.02). The prevalence of workers with high-normal BP and hypertension also decreased after those activities (−15% and −7%; p<0.001). The subjects who star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Patients without an initial diagnosis of hypertension and those who did not undergo regular follow-up assessments were excluded. The age and sex composition of the analyzed patient population was matched to that of patients with hypertension in Japan, as outlined in the JSH 2014 guidelines [8]; once the target proportion of men and women in the predefined age groups (20,30,40,50,60, 70, and 80 s) was reached, subsequent respondents were excluded from the analysis.…”
Section: Physicians and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients without an initial diagnosis of hypertension and those who did not undergo regular follow-up assessments were excluded. The age and sex composition of the analyzed patient population was matched to that of patients with hypertension in Japan, as outlined in the JSH 2014 guidelines [8]; once the target proportion of men and women in the predefined age groups (20,30,40,50,60, 70, and 80 s) was reached, subsequent respondents were excluded from the analysis.…”
Section: Physicians and Patientsmentioning
confidence: 99%
“…The most common explanations for this failure to control hypertension are insufficient patient lifestyle changes [14] and nonadherence to antihypertensive drugs, as well as treatment-resistant hypertension [15][16][17][18]. While knowledge of factors that contribute to nonadherence to lifestyle and therapeutic interventions is limited, it is widely believed that effective patient education (e.g., explanation of hypertension and the aims, effects and adverse effects of treatment, and good physician-patient relationships) is vital to improve BP control rates and achieve better patient quality of life and long-term clinical outcomes [8,15,[19][20][21]. The 2017 American College of Cardiology/American Heart Association, 2018 European Society of Cardiology/European Society of Hypertension, and JSH 2014 guidelines recommend team-based behavioral and motivational strategies to achieve healthy lifestyles [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…At the initial consultation, the majority of physicians (regardless of subgroup) acknowledged and provided education to patients on education items included in the 2014 JSH-guideline treatment strategy, such as the importance of adherence to treatment, reasons for treating hypertension and its associated complications, and educating patients about target BP [10]. Ensuring that patients received appropriate education around the benefits of good BP control has been shown to improve adherence to lifestyle and drug interventions [12][13][14][15][16]. In the current survey, specialists provided significantly more guidance to patients around lifestyle management factors than did nonspecialists in four key self-management areas: daily exercise (specialist: 83.1% vs nonspecialist: 64.5%, P < 0.01), weight reduction and maintenance (88.1% vs 62.0%, P < 0.001), decreased salt intake (89.8% vs 76.8%, P = 0.02), and moderation of alcohol intake (76.3% vs 49.2%, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of dissemination of cancer knowledge using printed materials has been reported in Japan, mainly in school education [19]. Although not cancer, the effectiveness of printed materials for health education focusing on hypertension management has been demonstrated, even in occupational elds [20]. A study that distributed health education materials to employees reported that women tend to read printed materials more than men [21].…”
Section: Development Of Educational Materials On Cervical Cancer For ...mentioning
confidence: 99%